Poverty Dynamics in Four OECD Countries - Antolín, Pablo (OECD Economics Department Working Papers, 1999)
This study examines the dynamics of poverty for four OECD countries (Canada, Germany, the United Kingdom and the United States). It provides information on patterns of poverty, which groups stay in poverty the longest, and household/individual characteristics and life-course events which appear to be most closely associated with transitions into and out of poverty and the length of time individuals stay in poverty. The analysis finds that the number of people touched by poverty over a six year period is significantly larger that the poverty rate might suggest, but the share of those staying poor for a long time is much smaller. The data suggest that longer-term poor are concentrated among women, lone parents and older single individuals. The study finds that employment status is the main factor affecting transitions into and out of poverty and the duration of poverty ...